A comparison of two structured taxonomic strategies in capturing adverse events in U.S. hospitals. (25th November 2018) - Austin, John M.; Kirley, Erin M.; Rosen, Michael A.; Winters, Bradford D.
Abstract : Objective: To compare the Agency for Healthcare Research and Quality's Quality and Safety Review System (QSRS) and the proposed triadic structure for the 11th version of the International Classification of Disease (ICD‐11) in their ability to capture adverse events in U.S. hospitals. Data Sources/Study Setting: One thousand patient admissions between 2014 and 2016 from three general, acute care hospitals located in Maryland and Washington D.C. Study Design: The admissions chosen for the study were a random sample from all three hospitals. Data Collection/Extraction Methods: All 1000 admissions were abstracted through QSRS by one set of Certified Coding Specialists and a different set of coders assigned the draft ICD‐11 codes. Previously assigned ICD‐10‐CM codes for 230 of the admissions were also used. Principal Findings: We found less than 20 percent agreement between QSRS and ICD‐11 in identifying the same adverse event. The likelihood of a mismatch between QSRS and ICD‐11 was almost twice that of a match. The findings were similar to the agreement found between QSRS and ICD‐10‐CM in identifying the same adverse event. When coders were provided with a list of potential adverse events, the sensitivity and negative predictive value of ICD‐11 improved. Conclusions: While ICD‐11 may offer an efficient way of identifying adverse events, our analysis found that in its draft form, it has a limited ability to capture the same types of events as QSRS. Coders may require additional training on identifying adverse events in the chart if ICD‐11 is going to prove its maximum benefit.